Parallel Changes in Mood and Melatonin Rhythm Following an Adjunctive Multimodal Chronobiological Intervention With Agomelatine in People With Depression: A Proof of Concept Open Label Study - Robillard, Rebecca; Carpenter, Joanne S.; Feilds, Kristy-Lee; Hermens, Daniel F.; White, Django; Naismith, Sharon L.; Bartlett, Delwyn; Whitwell, Bradley; Southan, James; Scott, Elizabeth M.; Hickie, Ian B. (Frontiers in Psychiatry, 2018)
Background Agomelatine is a melatonin agonist and 5HT antagonist developed for the treatment of major depressive disorder which also has some effects on the circadian system. Since circadian dysfunctions are thought to play a role in the pathophysiology of depression, some of the mechanism of action of this drug may relate to improvements in circadian rhythms. Objective This proof of concept open-label study sought to determine if improvements in depressive symptoms following an adjunctive multimodal intervention including agomelatine intake are associated with the magnitude of circadian realignment. This was investigated in young people with depression, a subgroup known to have high rates of delayed circadian rhythms. Methods Young people with depression received a psychoeducation session about sleep and circadian rhythms, were asked to progressively phase advance their wake up time, and completed an 8-week course of agomelatine (25-50 mg). Participants underwent semi-structured psychological assessments, ambulatory sleep-wake monitoring and measurement of melatonin circadian phase before and after the intervention. Results Twenty-four young adults with depression (17-28 years old; 58% females) completed the study. After the intervention, depressive symptoms were significantly reduced (t(23) = 6.9, p < .001) and, on average, the timing of dim light melatonin onset (DLMO) shifted 3.6 hours earlier (t(18) = 4.4, p < .001). On average, sleep onset was phase shifted 28 minutes earlier (t(19) = 2.1, p = .047) and total sleep time increased by 24 minutes (t(19) = -2.6, p = 0.018). There was no significant change in wake-up times. A strong correlation (r = .69, p = .001) was found between the relative improvements in depression severity and the degree of phase shift in DLMO. Conclusion Although this needs to be replicated in larger randomised controlled trials, these findings suggest that the degree of antidepressant response to a multimodal intervention including psychoeducation and agomelatine intake may be associated with the degree of change in evening melatonin release in young people with depression. This offers promising avenues for targeted treatment based on the prior identification of objective individual characteristics.